A novel approach for the development of photoluminescent material - Leite, E. R.; Pontes, F. M.; Lee, EJH; Aguiar, R.; Longo, Elson [UNESP]; Pontes, DSL; Nunes, MSJ; Macedo, H. R.; Pizani, P. S.; Lanciotti, F.; Boschi, T. M.; Varela, José Arana [UNESP]; et al. (Springer, 2002)
We report on several amorphous compounds based on different metal oxianions with intense photoluminescence at room temperature. These compounds were synthesised by a soft chemical process and deposited on Si (100) by a spin-coating technique. To select these different metal oxianions, a classic concept based on a metal oxide network former is used. We describe a minimum set of requirements to obtain an amorphous metal oxide with photoluminescence emission at room temperature.